The Effect of Sedentary Behaviour on Cardiorespiratory Fitness: A Systematic Review and Meta-Analysis - Prince, Stephanie A; Dempsey, Paddy C; Reed, Jennifer L; Rubin, Lukas; Saunders, Travis J; Ta, Josephine; Tomkinson, Grant R; Merucci, Katherine; Lang, Justin J (Sports medicine, 2024)
BACKGROUND: Cardiorespiratory fitness (CRF) is an important indicator of current and future health. While the impact of habitual physical activity on CRF is well established, the role of sedentary behaviour (SB) remains less understood. OBJECTIVE: We aimed to determine the effect of SB on CRF. METHODS: Searches were conducted in MEDLINE, Embase, PsycINFO, CINAHL and SPORTDiscus from inception to August 2022. Randomised controlled trials, quasi-experimental studies and cohort studies that assessed the relationship between SB and CRF were eligible. Narrative syntheses and meta-analyses summarised the evidence, and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) certainty was based on evidence from randomised controlled trials. RESULTS: This review included 18 studies that focused on youth (four randomised controlled trials, three quasi-experimental studies, 11 cohort studies) and 24 on adult populations (15 randomised controlled trials, five quasi-experimental studies, four cohort studies). In youth and adults, evidence from randomised controlled trials suggests mixed effects of SB on CRF, but with the potential for interventions to improve CRF. Quasi-experimental and cohort studies also support similar conclusions. Certainty of evidence was very low for both age groups. A meta-analysis of adult randomised controlled trials found that interventions targeting reducing SB, or increasing physical activity and reducing SB, had a significant effect on post-peak oxygen consumption (mean difference = 3.16 mL.kg-1.min-1, 95% confidence interval: 1.76, 4.57). CONCLUSIONS: Evidence from randomised controlled trials indicates mixed associations between SB and CRF, with the potential for SB to influence CRF, as supported by meta-analytical findings. Further well-designed trials are warranted to confirm the relationship between SB and CRF, explore the effects of SB independent from higher intensity activity, and investigate the existence of such relationships in paediatric populations. CLINICAL TRIAL REGISTRATION: PROSPERO CRD42022356218.
Keywords: Sedentary Behavior; randomizované kontrolované studie jako téma; Adult; Cardiorespiratory Fitness; dospělí; lidé; kardiorespirační zdatnost; cvičení; sedavý životní styl; Humans; Exercise; Randomized Controlled Trials as Topic